Gastronomía como atractivo turístico para el desarrollo de emprendimientos locales de la ciudad creativa de la Unesco – Portoviejo, Ecuador - Alcívar Arturo, Angélica Alexandra (2022)
The objective of the research was to design a gastronomic product as a tourist attraction for the development of local enterprises in the creative city of UNESCO-Portoviejo; it was structured under a mixed, non-experimental exploratory approach, made up of three phases: a tourism situational diagnosis, a market study, and the design, structure, and marketing of the gastronomic product. The study reflects that Portoviejo is characterized by its commercial activity; within the cultural resources in Manabi gastronomy, tourism managers agree that the vision regarding tourism should be changed since there are still deficiencies in the tourism system. There are 113 restaurants, in Abdón Calderón, blood sausage is a cultural identity attraction, empanadas is the typical dish of Alhajuela, in Crucita it is customary to hold the Seafood Festival, in Chirijos the Creole Chicken Festival is held, in Rio Chico Ceviche de Pinchagua stands out; the main competition of the destination is the Manta canton since it has a high level of uptake; the current demand is mostly national, from 18 to 28 years old, they arrive motivated by sun and beach tourism. The tourist product designed is based on a gastronomic route called "Between Flavors and Traditions", it runs through five parishes; for its commercialization, seven strategies were considered, highlighting the use of social networks, web pages, among others. The proposed tourism product will contribute to the development of enterprises, to value and publicize the typical gastronomy of Manabí, encouraging the socioeconomic development of Portoviejo.